(untitled) (Globalization and Business, 2023)
The COVID-19 pandemic has caused an economic crisis in almost every country in the world and has exacerbated economic, social, cultural, legal, educational, and other problems. Artificial intelligence, as the technology of the future, offers new ways to solve the problems of the post-pandemic period, to make technological decisions, to develop business processes using modern innovative advances, to improve management processes, to improve medical services opportunities, etc. Artificial intelligence is a field of special interest for researchers, one of the promising technologies of modern digital culture, which seeks not only to understand the nature of intelligence but also to create artificial systems with intelligent behavior. The potential of artificial intelligence can be harnessed in healthcare, agriculture, finance, energy, communications, economics, cybersecurity, and many more. However, artificial intelligence is associated with many risks, such as its use for criminal purposes, loss of jobs, or potential replacement. The main goal of the research is to determine the possibilities of introducing artificial intelligence systems in Georgia in the post-pandemic period, to select innovative approaches to increase economic efficiency and to find ways to solve the post-pandemic socio-economic problem. In the scientific paper, to determine the possibility of using artificial intelligence in the post-pandemic period and in-depth analysis of the current situation, both Georgian and foreign scientific literature, studies, and statistical data were studied. Using quantitative-statistical research methods, some conclusions and recommendations were developed based on the sharing of existing practices related to the use the artificial intelligence. Artificial intelligence plays a special role in the process of sustainable development of the post-pandemic economy and maximization of economic prosperity.